Rare case of massive inguinal dermatofibrosarcoma protuberans: A case report - Abdul Ahad Riaz; Faisal Naseer; Linta Malik; Allahdad Khan; Aseel Kamal; Mudasira Habib (Clinical Case Reports)
Key Clinical Message DFSP is a cutaneous soft tissue sarcoma. A 35 year old male patient presented with DFSP in the inguinal region which is a rare soft tissue sarcoma which usually presents in the torso, occurring very rarely in the inguinal region. Hence in case of any swelling in the inguinal region, DFSP should be in differential diagnosis.